2020
DOI: 10.1039/c9nr10235c
|View full text |Cite
|
Sign up to set email alerts
|

Photocarrier relaxation pathways in selenium quantum dots and their application in UV-Vis photodetection

Abstract: Selenium, as one of the chain-like materials, has attracted significant attention recently. Here, we investigated the photo-carrier dynamics in Se quantum dots and demonstrated its use for fast photo-detecting in visible regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…), which is 1.6, 2.0, 2.9, and 1.8 times higher than that of the Ni 78 Bi 22 , Ni 55 Bi 45 , Ni 23 Bi 77 , and monometallic Ni aerogel catalysts, respectively (Figure 19b). The Ni 97 Bi 3 aerogel also provides the highest specific activity, while the Ni 78 Bi 22 and Ni 55 Bi 45 aerogels exhibit comparable specific activities to the Ni aerogel (Figure 19b).…”
Section: −1mentioning
confidence: 87%
See 1 more Smart Citation
“…), which is 1.6, 2.0, 2.9, and 1.8 times higher than that of the Ni 78 Bi 22 , Ni 55 Bi 45 , Ni 23 Bi 77 , and monometallic Ni aerogel catalysts, respectively (Figure 19b). The Ni 97 Bi 3 aerogel also provides the highest specific activity, while the Ni 78 Bi 22 and Ni 55 Bi 45 aerogels exhibit comparable specific activities to the Ni aerogel (Figure 19b).…”
Section: −1mentioning
confidence: 87%
“…Nanoparticles are particles with a size range from 1 to 100 nm, which have attracted attractive scientific attention in a variety of fields, such as energy storage and conversion, [75][76][77] optics, [34,78] catalysis, [79][80][81] sensors, [82][83][84][85][86][87] biomedicines, [88][89][90][91][92] and so on, owing to their quantum effect. Liquid phase exfoliation (LPE) technique was often employed to fabricate 0D Bi QDs due to its low-cost, easy manipulation, and scalable production.…”
Section: D Bi Nanoparticlesmentioning
confidence: 99%
“…[ 59 ] In addition, the 2D Se nanosheets fabricated by liquid‐phase exfoliation, also exhibit obvious E 1 peak at 144.3 cm −1 and E 2 peak at 236.4 cm −1 (Figure 11e), [ 34 ] latter of which has a red shift compared to that of bulk Se, consistent with those of BP and antimonene nanosheets. [ 165,166 ] Moreover, 0D Se quantum dots fabricated by liquid‐phase exfoliation by Jiang et al, [ 61 ] also displays the single peak centered at ≈238 cm −1 , corresponding to the E 2 mode (Figure 11f).…”
Section: Properties and Applications Of Se Nanostructuresmentioning
confidence: 99%
“…Nanoparticles are particles with the size range of 1-100 nm, which have drawn attractive scientific attention due to their versatile potential applications in optical, electronic, and biomedical fields. [60][61][62][63][64][65][66][67][68][69] Qian et al [29] reported that Se nanoparticles with an average diameter of ≈3 nm and a narrow size distribution, were successfully fabricated in large quantities by liquid-phase exfoliation using NbSe 2 powders as the source material and N-methyl-2-pyrrolidone (NMP) as the dispersant (Figure 2a). High-resolution transmission electron microscopy (HRTEM) image (Figure 2a, inset) reveals that the as-prepared Se nanoparticles have the characteristic of crystalline lattice planes and the d-spacing is 0.23 nm.…”
Section: D Se Nanoparticlesmentioning
confidence: 99%
“…Generally, 0D nanomaterials refer to the particles with a size range of 1-100 nm. [99][100][101][102][103][104][105] As usual, the aggregation of 0D nanomaterials occurs to lower their high surface energies. Introducing 0D materials into 2D MXenes can comprehensively combine the advantages of both individual constituents and efficiently overcome their shortcomings.…”
Section: D Mxene/0d Nanomaterials Heterostructuresmentioning
confidence: 99%